PTPN18 promotes colorectal cancer progression by regulating the c-MYC-CDK4 axis - Chao Li; Shang-Ze Li; Xi-Cheng Huang; Jie Chen; Wenbin Liu; Xiao-Dong Zhang; Xue-Min Song; Run-Lei Du (Genes and Diseases, 2021)
Protein tyrosine phosphatase non-receptor type 18 (PTPN18) is often highly expressed in colorectal cancer (CRC), but its role in this disease remains unclear. We demonstrated that PTPN18 overexpression promotes growth and tumorigenesis in CRC cells and that PTPN18 deficiency yields the opposite results in vitro. Moreover, a xenograft assay showed that PTPN18 deficiency significantly inhibited tumorigenesis in vivo. PTPN18 activated the MYC signaling pathway and enhanced CDK4 expression, which is tightly associated with the cell cycle and proliferation in cancer cells. Finally, we found that MYC interacted with PTPN18 and increased the protein level of MYC. In conclusion, our results suggest that PTPN18 promotes CRC development by stabilizing the MYC protein level, which in turn activates the MYC-CDK4 axis. Thus, PTPN18 could be a novel therapeutic target in the future.